2001
DOI: 10.3748/wjg.7.5.735
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of rotaviral gastroenteritis with Qiwei Baizhu powder

Abstract: QWBZP has effects on improving the absorptive function of small intestine, shortening the duration of diarrhea and rotavirus shedding from stool and alleviating the pathological changes of small intestine induced by rotavirus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Baizhu-containing herbal medicine was also found to reduce replication of human rotavirus (HRV) and decrease the mortality of HRV-infected mice (He et al, 2001). In this study, another potential function of Baizhu was disclosed.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Baizhu-containing herbal medicine was also found to reduce replication of human rotavirus (HRV) and decrease the mortality of HRV-infected mice (He et al, 2001). In this study, another potential function of Baizhu was disclosed.…”
Section: Discussionmentioning
confidence: 91%
“…The rhizome of Baizhu is an important ingredient of several Chinese herbal prescriptions, and has been used in drugs for diarrhea, abdominal pain, and insufficiency of the stomach, intestine, liver, kidney, or insufficiency of the spleen with abundance of dampness (Wei et al, 1999). Recent reports have also demonstrated the inhibitory effect on the proliferation of human rotavirus (HRV) (He et al, 2001) and on the movement of uterus smooth muscles (Zhang et al, 2000) by Baizhu-containing herbal medicines or compounds from Baizhu. However, the anti-tumor effect of Baizhu has not been elucidated.…”
Section: Introductionmentioning
confidence: 96%
“…Antibody responses as well as CD4 + and CD8 + T cells are all involved in the protection against rotavirus infection in mice (Feng et al, 1994;Franco et al, 1997;McNeal et al, 2002). We have reported that QWBZP extract improves mucosa pathological changes, modulates the production of IFN-␥ and TNF-␣ in peripheral blood (Wu et al, 2002;Yang and Wu, 2005) as well as reduces mortality in mice after HRV infection (He et al, 1996(He et al, , 2001. In this study, we investigated the effects and mechanism of action of QWBZP on small intestinal mucosa epithelial cells in HRV infected mice.…”
Section: Introductionmentioning
confidence: 88%
“…The main active compounds of Baizhu are volatile oils such as hinesol, atractylone, and Rhizoma Atractylodis Macrocephalae lactone. These compounds have been used in drugs for abdominal pain, diarrhea, kidney, liver and spleen failure, inhibiting human rotavirus (HRV) replication and smooth uterine muscle movement (Zhang et al, 2000;He et al, 2001;Peng and Wang, 2004). Moreover, recent studies have shown that Baizhu has other medicinal properties such as anti-inflammatory activities (Li and He, 2006), inhibition of tumor cell proliferation (Huang et al, 2005;Liu et al, 2005), and suppression of diarrhea (Kim et al, 2005).…”
Section: Introductionmentioning
confidence: 99%